ANALISIS RESIDU ANTIBIOTIK TETRASIKLIN PADA DAGING AYAM BROIlER DAN DAGING SAPI - ary andini (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2019)
Tetracycline are antibiotics with broad-spectrum that used routinely in veterinary medicine for animal treatment and prevention from infectious diseases. But, consuming antibiotics for long time and exceeding standards can lead to accumulation of antibiotic residues in the body. Based on SNI 01-6366-2000, the maximum residual limit (BMR) of tetracycline antibiotic is 0.1 mg/kg in meat.The purpose of this study was to determine the concentration of tetracycline residues in broiler chicken meat and beef that obtained in East Surabaya namely Manyar market, Sinar Baru market, Ampengan Batu market, Tenggilis Mejoyo market, Krempyeng market, Soponyono market, and Gunung Anyar market. This study used Thin Layer Chromatography (TLC) as qualitative test and Spectrophotometric method as a quantitative test to determine the residual levels of tetracycline antibiotics. This study was conducted on March 15 onto May 2 2019. Based on the study, about 32 broiler chicken and 13 beef samples detected by the TLC method showed that had negative results, there was no containing tetracycline residues in samples. Awhile the results of the spectrophotometric method showed that as many as 31 samples of broiler chicken and 13 beef samples showed that had positive results containing residues of tetracycline antibiotics that exceed of the standard. Based on the results obtained that average concentration of tetracycline in samples of broiler chicken meat about 1,7 mg/kg and 0,8 mg/kg in beef samples. Descriptively,tetracycline residues in broiler chicken meat were higher than beef.